Effects of transcranial static magnetic field stimulation over the left dorsolateral prefrontal cortex on random number generation. (May 2023) - Soto-León, Vanesa; Díez-Rodríguez, Eva; Herrera-Pérez, Salvador; Rosa, Juliana M.; Aguilar, Juan; Hernando, Antonio; Bravo-Sánchez, Carlota; López-González, Verónica; Pérez-Borrego, Yolanda; Bestmann, Sven; Oliviero, Antonio
Highlights: We assessed the effects of single-session transcranial static magnetic field stimulation (tSMS) over left dorsolateral prefrontal cortex (DLPFC) on randomness. Randomness index on a random number generation task increased few minutes after tSMS application. tSMS over left DLPFC of healthy subjects can interfere with normal brain function. Abstract: Objective: Focal application of transcranial static magnetic field stimulation (tSMS) is a neuromodulation technique, with predominantly inhibitory effects when applied to the motor, somatosensory or visual cortex. Whether this approach can also transiently interact with dorsolateral prefrontal cortex (DLPFC) function remains unclear. The suppression of habitual or competitive responses is one of the core executive functions linked to DLPFC function. This study aimed to assess the impact of tSMS on the prefrontal contributions to inhibitory control and response selection by means of a RNG task. Methods: We applied 20 min of tSMS over the left DLPFC of healthy subjects, using a real/sham cross-over design, during performance of a RNG task. We used an index of randomness calculated with the measures of entropy and correlation to assess the impact of stimulation on DLPFC function. Results: The randomness index of the sequences generated during the tSMS intervention was significantly higher compared to those produced in the sham condition. Conclusions: Our results indicate that application of tSMS transiently modulates specific functional brain networks in DLPFC, which indicate a potential use of tSMS for treatment of neuropsychiatric disorders. Significance: This study provides evidence for the capacity of tSMS for modulating DLPFC function.